Associations between biomarkers of environmental enteric dysfunction and oral rotavirus vaccine immunogenicity in rural Zimbabwean infants - James A Church (Elsevier, 2021)
Background: Oral rotavirus vaccines (RVV) are poorly immunogenic in low-income countries. Environmental enteric dysfunction (EED) resulting from poor water, sanitation and hygiene (WASH) may contribute. We therefore tested associations between EED and RVV immunogenicity, and evaluated the effect of improved WASH on EED. Methods: We measured nine biomarkers of EED among Zimbabwean infants born to mothers enrolled in a cluster-randomised 2 × 2 factorial trial of improved WASH and improved feeding between November 2012 and March 2015 (NCT01824940). We used multivariable regression to determine associations between EED biomarkers and RVV seroconversion, seropositivity and geometric mean titer. Log-binomial regression was used to evaluate the effect of improved WASH on EED. Findings: Among 303 infants with EED biomarkers and immunogenicity data, plasma intestinal fatty-acid binding protein and stool myeloperoxidase were positively associated with RVV seroconversion; adjusted RR 1.63 (95%CI 1.04, 2.57) and 1.29 (95%CI 1.01, 1.65), respectively. There were no other associations between RVV immunogenicity and either individual biomarkers or EED domains (intestinal permeability, intestinal damage, intestinal inflammation and microbial translocation). EED biomarkers did not differ between randomised WASH and non-WASH groups. Interpretation: We found no evidence that EED was associated with poor RVV immunogenicity. Contrary to our hypothesis, there was weak evidence that EED was associated with increased seroconversion. EED biomarkers were not affected by a package of household-level WASH interventions.